Supply chain benchmarking : visualisation of performance - Lee, Guan Bin (2014)
The production and life cycles for new products are getting shorter. Suppliers, production centers, logistics networks and customer bases are becoming more global in nature. Hence good Supply Chain Management (SCM) practices become increasingly important for businesses. A business must be able to identify, track, and manage its SCM Key Performance Indicators (KPIs) so that it can provide timely and reliable delivery of its products. Having a set of SCM KPIS will also enable a business to perform benchmarking to improve practices and performance so that it’s SCM can be a competitive advantage.